ESTIMATES OF ENERGY AND PROTEIN FRACTIONS OF CROP RESIDUE BASED COMPLETE RATIONS - K. Raja Kishore; D. Srinivas Kumar; J.V. Ramana; A. Ravi; E. Raghava Rao (Indian Journal of Veterinary and Animal Sciences Research, 2024)
A study was undertaken to evaluate carbohydrate and protein fractions of crop residue based complete rations as per the procedure of Cornel Net Carbohydrate and Protein (CNCPs) system.  Three iso-nitrogenous complete rations were prepared comprising of maize stover (T1) straw , red gram straw (T2) and black gram (T3) and concentrate mixture in 60: 40 ratio, respectively and were analyzed for CNCPS fractions. Maize stover contained lower (P